Jersey fracture: Avulsion-fracture injury of the flexor digitorum profundus - Maikel Falcon; Gary M. Vilke (JEM Reports)
Closed avulsion injuries of the flexor digitorum profundus (FDP) from the insertion at the base of the distal phalanx are not a very common lesion but when they occur, tend to be related to sport injuries. Though the diagnosis is made clinically, radiographs need be performed. Prompt surgical treatment within 7 to 14 days is the first line option to assure good outcomes.